«MICROSOFT PROJECT» - INFORMATION TECHNOLOGY OF REDUCED FLIGHT CREW - Горбунов, В. (Science-based technologies, 2011)
The technique of the application of information technology «Microsoft Project» was developed for the analytical analysis of remedial opportunities of safe piloting the plane by the reduced flight crew. It allows to reveal the factors, which reduce the safety of flight because of the lack of time and demand the additional resources of crew or are characterized by overwork of its individual members.